Implementation simulink modeling to analysis the transient cases and torque speed characteristic in a three phase induction motors - Omar Al-barbarawi; Ghazi M. Qaryouti (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this research, has been a developed  modular approach  for investigation of the dynamic behavior and analysis the steady -state and transient cases  for a three-phase induction motor when it is fed with a balanced and unbalanced voltage , and analysis the  behavior of the Torque-Speed characteristics at various conditions. This analysis is done systematically by development two mathematically models. Where the first model is proposed   to simulate the dynamic behavior of the motor when supplying it at balanced and unbalanced voltage in Matlab/Simulink by using d-q axis theory in the reference frame. This model can investigate and described in details the behavior of the induction motor  parameters, and enables the researcher to calculate or investigate any variable for an induction machine  parameter ; (e.g. The  voltage, current, flux, speed and torque as a function of time) in both cases  transient and steady state , when the motor in operation state  [11-16].  The other model is proposed to simulate in the Microsoft Excel program, by using  the ratio between the conventions  of the electromagnetic torque equation(Tem)  and maximum torque equation (Tmax) . To study and analysis the behavior of the Torque-Speed characteristics for a 3-phase induction motor. Where this models study's by using Excel program's and Matlab / Simulink to simulation the effect of the various parameters on the dynamic behavior of the motor such as  inserting variable external resistance in series with rotor circuit , and when supplying the stator by variable voltage. These Mathematical models could be   used for a wide range of motors which has a various horse powers , which needing it in a scientific research and practical applications.